THE IMPACT OF THE TIKTOK APP ON STUDENTS' BEHAVIOR TOWARD TEACHERS - Fitriyanti Fitriyanti; Rahayu Suprapti; Annisa Astrid; Arvin Efriani (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to describe the intensity of TikTok application use and analyze its influence on the morals of ninth-grade students toward teachers at SMPN 1 Talang Kelapa. The background of this research stems from the increasing use of TikTok among teenagers, which has the potential to affect behavior and moral values in interactions with teachers. The study uses a quantitative approach with a descriptive-correlational method. The sample consists of 60 students selected through purposive sampling techniques. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, then analyzed using Pearson correlation and simple linear regression with the help of SPSS version 26. The results show that the intensity of TikTok use is categorized as high (mean = 78.45), while students’ morals toward teachers are categorized as fairly good (mean = 68.12). The correlation test resulted in r = -0.612 (p = 0.000), indicating a significant negative relationship between the two variables. The regression results show R² = 0.375, meaning that TikTok usage influences 37.5% of students’ morals. Thus, the higher the intensity of TikTok use, the lower the students’ morals toward teachers. Cooperation among teachers, parents, and the school is needed in character development and digital literacy so that social media can be used positively.